2020
DOI: 10.3390/su12239873
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Potential Evaluation of Concrete with Steel Slag Aggregates by the LCA Method

Abstract: Sustainability in the construction industry refers to all resource-efficient and environmentally responsible processes throughout the life cycle of a structure. Green buildings may incorporate reused, recycled, or recovered materials in their construction. Concrete is as an important building material. Due to the implementation of by-products and waste from various industries into its structure, concrete represents a significant sustainable material. Steel slag has great potential for its reuse in concrete pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…One cubic meter of designed paste with compressive strength of about 60 MPa is considered a functional unit, so material and emission flow related to its production can be included in the scope of the analysis. The emission data and consumed energy necessary for the inventory were compiled from the literature review [ 28 , 29 , 30 , 31 ], theoretical estimations, and Ecoinvent database v3.4 by using SimaPro SW 9.0.…”
Section: Methodsmentioning
confidence: 99%
“…One cubic meter of designed paste with compressive strength of about 60 MPa is considered a functional unit, so material and emission flow related to its production can be included in the scope of the analysis. The emission data and consumed energy necessary for the inventory were compiled from the literature review [ 28 , 29 , 30 , 31 ], theoretical estimations, and Ecoinvent database v3.4 by using SimaPro SW 9.0.…”
Section: Methodsmentioning
confidence: 99%
“…Václavík et al replaced natural aggregates with steel slag in cement concrete and investigated associated environmental impacts using an LCA. The results showed that steel slag aggregate can diminish 7% of environmental burdens [24]. Anastasiou et al considered the sustainability of utilizing industrial by-products (fly ash and steel slag) in cement mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the use of the coarse fraction of EAFS can produce hydraulic concrete with adequate mechanical [18] and durability properties [19], increasing the sustainability of the resulting product [20]. The use of the fine fraction without any fine natural aggregate is also suitable for concretes that do not require high workability, due to the scarcity of fine particles in EAFS [14].…”
Section: Introductionmentioning
confidence: 99%